EPISTEMOLOGY OF SUFISM AND THE WITNESS OF SYEKH ABDUL QADIR AL-JAILANI AND ITS IMPLICATIONS FOR THE TREASURE OF ISLAMIC THOUGHT - Aminudin; Masykur Arif (Living Sufism: Journal of Sufism and Psychotherapy, 2025)
Sheikh Abdul Qadir al-Jailani is a great Sufi figure widely known in the Sunni Sufism tradition. His thoughts and teachings not only formed the map of classical Islamic spirituality, but also made important contributions to the construction of Sufism epistemology and the concept of guardian. This study discusses in depth how the epistemology of Sufism was developed by Sheikh Abdul Qadir al-Jailani, emphasizing the sources of spiritual knowledge such as kasyf, ilham, and ma'rifah, as well as how the concept of sainthood is interpreted as the highest realization of the human spiritual journey. Furthermore, this article also explores how his legacy of thought has implications for the development of Islamic thought in the modern era, particularly in responding to the crisis of spirituality and materialistic tendencies that are developing in the contemporary world. With a qualitative approach and hermeneutic analysis of the works of Sheikh Abdul Qadir al-Jailani such as Futuh al-Ghaib and al-Fath al-Rabbani, this paper shows that the epistemology of Sufism can be an alternative in building a more holistic, integrative, and transcendental scientific paradigm. Ultimately, Sheikh Abdul Qadir's thoughts are not only relevant as a spiritual legacy, but also as an offer of solutions for modern Islamic civilization which is seeking a balance between rationality and spirituality.